2015
DOI: 10.1111/febs.13237
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a detailed kinetic model of glycolysis in Plasmodium falciparum

Abstract: The enzymes in the Embden-Meyerhof-Parnas pathway of Plasmodium falciparum trophozoites were kinetically characterized and their integrated activities analyzed in a mathematical model. For validation of the model, we compared model predictions for steady-state fluxes and metabolite concentrations of the hexose phosphates with experimental values for intact parasites. The model, which is completely based on kinetic parameters that were measured for the individual enzymes, gives an accurate prediction of the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 120 publications
0
40
0
Order By: Relevance
“…Projects of all sizes can be registered; from large, multinational consortia to those undertaken by individual researchers. An example of a published (3) collection of data and models is the ‘Glucose metabolism in Plasmodium falciparum trophozoites’ investigation (https://fairdomhub.org/investigations/56) that has 3 Studies, 24 Assays, 16 Data files, 19 Models, 13 SOPs and 3 Publications. The Investigation describes the construction, analysis and validation of a model of glycolysis in the malaria parasite P. falciparum .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Projects of all sizes can be registered; from large, multinational consortia to those undertaken by individual researchers. An example of a published (3) collection of data and models is the ‘Glucose metabolism in Plasmodium falciparum trophozoites’ investigation (https://fairdomhub.org/investigations/56) that has 3 Studies, 24 Assays, 16 Data files, 19 Models, 13 SOPs and 3 Publications. The Investigation describes the construction, analysis and validation of a model of glycolysis in the malaria parasite P. falciparum .…”
Section: Methodsmentioning
confidence: 99%
“…For publication, digital object identifiers (DOI) can be minted for individual assets or for a collection that forms part of an investigation (e.g. DOI: 10.15490/seek.1.investigation.56, which is referenced in (3)). This means that content can be directly cited by researchers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Snoep and colleagues, the authors first measured the specific activity of every glycolytic enzyme at a single reference physiological pH and temperature in cell-free extracts of P. falciparum trophozoites [4]. They also measured the activities of glucose, pyruvate and lactate transporters under these conditions.…”
Section: Constructing a P Falciparum-specific Mathematical Model Of mentioning
confidence: 99%
“…Penkler et al [85] nicely showed how a modeling study can be described and published in a reproducible manner, using standard formats and the SEEK platform. Their model code is available, together with raw data, simulation setups and result data.…”
Section: B Depositing Reproducible Modelsmentioning
confidence: 99%